The child witness in the accusatorial system - Müller, Karen, 1964- (Rhodes University, Faculty of Law, Law, 1998)
For the purpose of this study tbe child witness in the accusatorial system will be viewed as a source of information. When a witness gives evidence in court, the function of the witness is to provide the court with certain information. A number of crucial questions arise when the witness is a child. Do children bave the ability to remember and relate an event accurately? Are children prone to suggestion and fantasy? What effect, if any, does the court environment have on a child 's ability to convey information? What perceptions do children have about the legal process, and how do these perceptions affect their ability to testify? Do adults influence the information which children impart by the techniques they employ to obtain such information? Accepting the hypothesis that child witnesses are sources of information, the purpose of this study is to evaluate all aspects of the criminal justice system relating to child witnesses as well as available research on children to determine whether it is possible to obtain reliable and accurate information from children. Proposals will be formulated regarding the most successful methods of obtaining reliable and accurate information from children, and how these can be adapted for use by the legal system. The purpose of the study is to develop an approach to children in the legal system that will be fair to children while at the same time protecting the rights of the accused, and which will lead to a successful method of obtaining accurate information.
Keywords: Child witnesses; Children -- Legal status, laws, etc.; Child witnesses -- South Africa; Evidence (Law)